Beyond Erythema Infectiosum: A Rare Case of Parvovirus B19 with Neurological, Renal, Hematological & Cardiac Manifestations - Jerin, Nusrat Jahan; Hena, Rashida Tanjum; Sabah, Munjarin; Alam, Mohammad Jahangir Ul; Chowdhury, Shahabul Huda (Journal of Medicine, 2025)
Acute Parvovirus B19 infection can lead to severe neurological and systemic complications. This case describes a rare presentation of Parvovirus B19 encephalitis with posterior reversible encephalopathy syndrome (PRES) with symptomatic seizure accompanied by dilated cardiomyopathy (DCM) with atrial septal defect-secundum, acute kidney injury (AKI), sepsis and pure red cell aplasia (PRCA). The complex interplay of these conditions posed significant diagnostic and management challenges. Neurological involvement manifested as encephalitis with PRES, contributing to symptomatic seizures and progressing to status epilepticus. The concurrent development of DCM and AKI suggested a profound systemic inflammatory response, exacerbated by sepsis. PRCA further complicated the clinical course by inducing severe anemia. This case highlights the need for early recognition, comprehensive monitoring, and multidisciplinary intervention to improve patient outcomes in severe Parvovirus B19 infections with multi- organ involvement. J MEDICINE 2025; 26(2): 146-151